Book Review: Byzantine War Ideology between Roman Imperial Concept and Christian Religion. Akten des Internationalen Symposiums (Wien, 19.-21. Mai 2011), Vienna 2012 - STEPHENSON, Paul (Byzantina Symmeikta, 2014)
Book review: Byzantine War Ideology between Roman Imperial Concept and Christian Religion. Akten des Internationalen Symposiums (Wien, 19.-21. Mai 2011).Veröffentlichungen zur Byzanzforschung, Band XXX, eds. J. Koder and I. Stouraitis, Vienna 2012. pp. 137. ISBN: 9783700173076